The use of capreomycin in the treatment of tuberculosis - Kuryan, O.O.; Poshtarenko, A.V.; Reshetnyak, L.R. (Problems of Environmental Biotechnology, 2023)
In 2021, tuberculosis remains an urgent problem in Ukraine and the world, in particular multidrug-resistant tuberculosis (MDR-TB), which poses an extreme threat to public health. Capreomycin, as the main drug for the treatment of MDR-TB, is known for its high toxicity and long course of administration. The use of the inhalation form of delivery of capreomycin allows to achieve high concentrations of the drug in the lungs, while reducing its systemic effect. Studies in healthy adults indicate that capreomycin inhalation dry powder is well tolerated, with only mild to moderate shortterm cough in some patients as the main adverse reaction. This approach can significantly improve the effectiveness of MDR-TB treatment and reduce the risk of side effects for patients, providing a safer and more effective way to fight this dangerous disease.